2020
DOI: 10.1177/1559325820946934
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Urinile Against Gouty Arthritis

Abstract: Gout is arthritis caused due to Monosodium urate (MSU) crystals deposition occurring particularly in patients with associated comorbidities limiting the use of conventional therapies. This study was planned to evaluate the therapeutic efficacy of urinile (a herbal drug) for the treatment of gouty arthritis. Allopurinol was used as standard drug (positive control). The study population of 250 volunteers (gouty arthritis patients) were divided into 2 groups as test and control group (n = 125 each). Gouty arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The BuOH fraction also exhibited considerable XO inhibitory activity, with an inhibition percentage of 69.43 ± 8.68 % at 100 µg/mL, slightly lower than the EtOAc fraction, which also signifies a substantial inhibitory effect, as reported by previous XO inhibitory research ( Noor Hashim et al, 2013 ). Furthermore, the EtOAc and BuOH fractions from D. spathacea showed concentration-dependent inhibition of XO, as evidenced by their differing activities at 100 µg/mL and 50 µg/mL, similar to the inhibitory potential against XO depending on the concentration of Alocasia longiloba , Urinile ( Ahmad et al, 2020 , Alam et al, 2021 ). The hexane fraction displayed the lowest XO inhibitory activity of 27.11 ± 2.50 % at 100 µg/mL among the fractions tested ( Supplementary data Table 2S ), so this fraction was not subjected to further research.…”
Section: Discussionmentioning
confidence: 78%
“…The BuOH fraction also exhibited considerable XO inhibitory activity, with an inhibition percentage of 69.43 ± 8.68 % at 100 µg/mL, slightly lower than the EtOAc fraction, which also signifies a substantial inhibitory effect, as reported by previous XO inhibitory research ( Noor Hashim et al, 2013 ). Furthermore, the EtOAc and BuOH fractions from D. spathacea showed concentration-dependent inhibition of XO, as evidenced by their differing activities at 100 µg/mL and 50 µg/mL, similar to the inhibitory potential against XO depending on the concentration of Alocasia longiloba , Urinile ( Ahmad et al, 2020 , Alam et al, 2021 ). The hexane fraction displayed the lowest XO inhibitory activity of 27.11 ± 2.50 % at 100 µg/mL among the fractions tested ( Supplementary data Table 2S ), so this fraction was not subjected to further research.…”
Section: Discussionmentioning
confidence: 78%
“…Besides, quercetin and kaempferol may significantly elevate the total antioxidant capacity and inhibit the xanthine oxidase (XOD) effect in hyperuricemia rats [ 28 ]. In another study, inhibition of XOD activity could reduce the serum uric acid level and the formation of ROS, consequently reducing the deposition of gout urate crystals [ 29 ]. Additional studies found that quercetin could reduce serum uric acid levels in hyperuricemia mice and impede renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Polyherbal formulation Urinile is composed of Berberis vulgaris, Ajwain (Trachyspermum ammi), Suranjan Shirin and Karafs (Apium graveolens). 22 In a standard controlled, comparative study to evaluate the efficacy of Polyherbal Unani formulation on hyperurecemia, 100 patients were allocated randomly to two groups. The efficacy of the test treated medication (Gouticin) was superior at p < 0.05.…”
Section: Recent Researchesmentioning
confidence: 99%